Optical Communications and Networking: Prospects in Industrial Applications - Bao, Changjing (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
In the past few decades, the optical communication industry has explored multiple degrees of freedom of the photon, such as time, wavelength, amplitude, phase, polarization, and space, to significantly reduce the cost/bit of data transmission by increasing the capacity per fiber through multiplexing technology and by reducing the size and power through electronic and photonic integration. This book aims to explore the latest advancements in this industry, including the technologies in devices, systems, and network levels with applications from short-reach chip-to-chip interconnections to long-haul backbone communications at the trans-oceanic distance.